Reduction in opioid use and postoperative pain scores after elective laparotomy with implementation of enhanced recovery after surgery protocol on a gynecologic oncology service. Issue 5 (2nd May 2019) - Schwartz, Amanda Rae; Lim, Stephanie; Broadwater, Gloria; Cobb, Lauren; Valea, Fidel; Marosky Thacker, Julie; Habib, Ashraf; Havrilesky, Laura
Abstract : Objective: Enhanced Recovery After Surgery (ERAS) protocols are designed to mitigate the physiologic stress response created by surgery, to decrease the time to resumption of daily activities, and to improve overall recovery. This study aims to investigate postoperative recovery outcomes following gynecologic surgery before and after implementation of an ERAS protocol. Methods: A retrospective chart review was performed of patients undergoing elective laparotomy at a major academic center following implementation of an ERAS protocol (11/4/2014–7/27/2016) with comparison to a historical cohort (6/23/2013–9/30/2014). The primary outcome was length of hospital stay. Secondary outcomes included surgical variables, time to recovery of baseline function, opioid usage, pain scores, and complication rates. Statistical analyses were performed using Wilcoxon rank sum, Fisher's exact, and chi squared tests. Results: One hundred and thirty-three women on the ERAS protocol who underwent elective laparotomy were compared with 121 historical controls. There was no difference in length of stay between cohorts (median 4 days; P = 0.71). ERAS participants had lower intraoperative (45 vs 75 oral morphine equivalents; P < 0.0001) and postoperative (45 vs 154 oral morphine equivalents; P < 0.0001) opioid use. ERAS patients reported lower maximum pain scores in the post-anesthesia care unit (three vs six; P < 0.0001) and on postoperative day 1 (four vs six; P = 0.002). There was no statistically significant difference in complication or readmission rates. Conclusions: ERAS protocol implementation was associated with decreased intraoperative and postoperative opioid use and improved pain scores without significant changes in length of stay or complication rates.